Attention Deficit Hyperactivity Disorder (ADHD) and Associated Factors Among First-Year Elementary School Students - Hoang, Hai Huu (J Multidiscip Healthc, 2021)
PURPOSE: Attention deficit hyperactivity disorder (ADHD) is a mental health disorder commonly in children. This study aimed to examine the prevalence of ADHD and risk factors among first-year pupils in Vietnam’s urban city. PATIENTS AND METHODS: A cross-sectional study was conducted in four randomly selected primary schools. Information on 525 pupils in grade 1 (ages 6 to 7 years) was collected from 525 parents/caregivers and 28 teachers. We used the Vanderbilt Assessment Scales with two separate versions for parents and teachers to screen children with ADHD symptoms. RESULTS: Among the total of 525 pupils, 24 (4.6%) were found to have ADHD symptom types (boy: 6.5%; girl: 2.1%). The combined ADHD type accounted for the highest proportion of 3.4%, followed by predominantly inattentive and predominantly hyperactivity type. ADHD prevalence rated by teachers was higher than those rated by parents. High agreement between parents and teachers was reported (κ > 0.6). The risk of ADHD increased in male participants (aOR=4.90, 95% CI 1.51–15.85), those having a first-degree relative with ADHD (aOR=85.2, 95% CI 1.66–4371.8), in-utero exposure to tobacco smoke (aOR=4.78, 95% CI 1.31–17.44), and prenatal alcohol drinking (aOR=8.87, 95% CI 2.29–34.42). CONCLUSION: These findings suggest the importance of ADHD screening for pupils attending elementary schools, particularly those with a family history of ADHD. Public health programs should reduce prenatal exposure to the potential risk factors of ADHD (smoking and alcohol consumption).